2019
DOI: 10.1177/0972753119887321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taping of Thoracic and Abdominal Muscles on Pelvic Alignment and Forward Reach Distance Among Stroke Subjects: A Randomized Controlled Trial

Abstract: Introduction: The objective of this study was to find the immediate as well as short-term effect on pelvic alignment and forward arm reach distance in sitting among stroke patients following thoracic spine and abdominal muscles taping along with conventional therapy. Methods: Thirty subjects with stroke attending the physiotherapy programme at Department of Physiotherapy at a tertiary care hospital underwent this randomized controlled experimental study. Subjects in the experimental group received taping, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These studies were also conducted in stroke patients. Mehta et al reported that when taping was attached to the thoracic and abdomen of stroke patients, the pelvic obliquity and anterior pelvic tilt in a sitting position were improved compared to the control group, which resulted in improved balance [20]. In addition, one study reported that posterior pelvic tilt taping significantly improved pelvic anterior tilt, gait speed, and step length in stroke patients, but further studies are needed as the long-term effects have not been confirmed [21].…”
Section: Introductionmentioning
confidence: 99%
“…These studies were also conducted in stroke patients. Mehta et al reported that when taping was attached to the thoracic and abdomen of stroke patients, the pelvic obliquity and anterior pelvic tilt in a sitting position were improved compared to the control group, which resulted in improved balance [20]. In addition, one study reported that posterior pelvic tilt taping significantly improved pelvic anterior tilt, gait speed, and step length in stroke patients, but further studies are needed as the long-term effects have not been confirmed [21].…”
Section: Introductionmentioning
confidence: 99%
“…Taping approximately 5 cm wide on the rectus abdominis and external oblique abdominal muscles 36 or on the thoracic spine and abdominal muscles to improve posterior PT. 37 These methods can potentially optimize the relationship between muscle length and tension as taping can continuously pull the fascia concentrically and shorten the distance between the origin and insertion of the muscle. 38 In the future, we would like to consider the use of taping as one of the treatment options to improve SAD.…”
Section: Discussionmentioning
confidence: 99%
“…Mehta et al reported that due to attaching tapings to the thoracic spine and abdominal muscles in patients with stroke, anterior pelvic tilt, and pelvic obliquity were significantly improved in a sitting position. They argued that more abdominal muscles were recruited as taping improved the active musculotendinous and neural control components of the spine stabilizing system [ 20 ]. Also, in a study in which taping was attached to the back muscle in children with cerebral palsy, the kyphosis angle and Gross Motor Function Measure Sitting score were significantly improved compared to the control group [ 21 ].…”
Section: Introductionmentioning
confidence: 99%